Role of Calcium in Maintenance of Postharvest Quality of Horticultural Crops - Abrol, Ghan Shyam; Thakur, K. S.; Pal, Ranjit; Punetha, Shailja (International Journal of Economic Plants, 2017)
Horticulture has emerged as one of the major agricultural sectors as there has been a substantial increase both in area and production of horticulture crops. But still the wastage losses in horticulture are major concern. Minimizing these losses can increase their supply without bringing additional land under cultivation is necessary. Preharvest applications of calcium mainly in form of calcium chloride can modify biochemical changes occurring within developing fruits and therefore has a potential to transform its quality at harvest, which can ultimately affect storage quality of fruits. It is one of essential nutrient for maintaining the structure and function of cell wall and membranes as it interacts with pectic acid in the cell wall to form calcium pectate, thereby having a direct influence on fruit firmness. Calcium also has beneficial effects on marketing and storage of fruits through inhibition of abnormal senescence and reduction of respiration rate, ethylene synthesis, protein breakdown, weight loss and rotting. It has also been reported that fruits high in calcium have lower respiration rates.